Relationship between Cysteine, Interleukin (IL)-2, And Interleukin (IL)-10 in Children with Marasmus Type Malnutrition - Wahyudi, Teguh; Puryatni, Anik; Hernowati, Tinny Endang (Journal of Tropical Life Science, 2016)
Malnutrition is one of the health issues in developing countries. The most commonly found malnutrition is the marasmus type. Infection in marasmus patient is the main cause of morbidity and mortality in developing countries. In marasmus, there is a decrease in protein level such as cysteine which is one of the glutathione forming components that plays a significant role in immune system. In malnutrition, there is a disturbance of lymphocyte in the form of down-regulation of type 1 cytokine (IL-2 and IFN-γ) and up- regulation of type 2 cytokine (IL-4 and IL-10). IL-2 is needed for the development of regulatory T produced by thymus and for NK cell cytotoxicity which plays a role in infection process, while IL-10 inhibits activation of lymphocyte T so the cellular immunity reaction ends. Several studies about the relationship between cysteine, IL-2, and IL-10 have been done in malnutrition-patients, but there is no study focusing on patients with marasmus. This study is to find out the relationship between cysteine, IL-2, and IL-10 in patients with marasmus type malnutrition. This study was an observational analytic study using cross-sectional design consisting of 20 children with marasmus type malnutrition and 20 well-nourished children treated in Saiful Anwar Hospital Malang. The cysteine, IL-2, and IL-10 level then measured using Elisa method. Normality and the various test were done. The Pearson correlation test was done to find out the relationship between cysteine and IL-2 level, cysteine and IL-10 level, and IL-2 and IL-10. The standard of cysteine and IL-2 level in children with marasmus is significantly lower than the control group, which was 1.616 ± 1.039 vs 3.298 ± 0.519 pg/mL; p = 0.000 dan 12.38±4.94 vs. 16.58 ± 4.80 pg/mL;p = 0.010, respectively. IL-10 in children with marasmus was significantly higher than control group (19.08± 5.93 vs 10.46 ± 3.90 pg/mL; p = 0.000). The cysteine level was positively correlated to the IL-2 level (p = 0.000; r = 0.71), while the cysteine and IL-10, IL-2 and IL-10 was negatively correlated with p = 0.014; r= -0.53 and p=0.037; r= -0.46 in marasmus. There was a positive correlation between the cysteine and IL-2 level and negative correlation between IL-10 and IL-2 also IL-2 and IL-10 in children with marasmus.